O envolvimento do departamento de compras no processo de contratação de serviços profissionais - Pereira, Gustavo Menoncin de Carvalho (2013)
Theory about the activity of Procurement argues that companies should delegate to this area the activity to purchase materials and services. The goal is to achieve competitiveness without losing the quality due to competence and expertise through this area. In many companies this area is not involved in all situations of contracting processes. Few articles and published papers studies the relationship of the internal customer with the Purchasing Department. This thesis aims to identify problems that interfere with involving the purchasing department in procurement processes of professional services. Agency theory is used as theoretical support, as it is a relation of a Principal, the internal customer and an agent, the purchasing department. The hypotheses tested were tested to verify if involving the Purchasing Department differs by category and the relation with premises of the Agency Theory. The quantitative survey had 519 responses from national and multinational companies in Brazil, from various sectors of the economy. (367 from internal customers and 152 from purchasing professionals). Scales used in previous works have been validated, and the data were analyzed from the results of analysis of variance and multiple regression. The questionnaire was available on the Internet to the internal customers of the Purchasing Department, in order to focus on why the non-involvement of the department. The results indicate that the perception of internal customers about involvement of the purchasing department differs by type of professional service. The relationship between the dimensions of involvement with the premises of the Agency theory was confirmed. Responses received from purchasing professionals confirm that perceptions about the involvement of the purchasing department differ when comparing the answers with internal clients. The theoretical contribution was the use of agency theory to study problems in the supply chain, and validation of scales and production research in categories not specifically related to the production. In the field of management, the results explain the relationship between the four dimensions of involvement and Agency Theory and present the differences by category of involvement to be hired.